A Generic Embedding Class-I Model via Karmarkar Condition in fℛ, T Gravity. (9th February 2021) - Zubair, M.; Waheed, Saira; Javaid, Hina
Abstract : In the present work, we investigate the existence of compact star model in the background of f ℛ, T gravity theory, where ℛ represents the Ricci scalar and T refers to the energy-momentum tensor trace. Here, we use Karmarkar condition for the interior stellar setup so that a complete and precise model following the embedding class-I strategy can be obtained. For this purpose, we assume anisotropic matter contents along with static and spherically symmetric geometry of compact star. As Karmarkar embedding condition yields a relationship of metric potentials, therefore we assume a suitable form for one of the metric components as e ϕ = a r 2 + b n − 1 r n + 1, where a and b represent constants and n is a free parameter, and evaluate the other. We approximate the values of physical parameters like a, A, and B by utilizing the known values of mass and radius for the compact star Vela X-1. The validity of the acquired model is then explored for different values of coupling parameter λ graphically. It is found that the resulting solution is physically interesting and well-behaved.